A holistic DPSIR-based approach to the remediation of heavily contaminated coastal areas. (1st September 2021) - Labianca, Claudia; De Gisi, Sabino; Todaro, Francesco; Wang, Lei; Tsang, Daniel C.W.; Notarnicola, Michele
Abstract: This paper proposes a holistic approach to connect anthropogenic impacts to environmental remediation solutions. The eDPSIR (engineered-Drivers-Pressures-States-Impacts-Responses) framework aims at supporting the decision-maker in designing technological solutions for a contaminated coastal area, where the natural matrices need to be cleaned up. The eDPSIR is characterized by cause-effect relationships that are operationally implemented through three multidisciplinary toolboxes: (i) Toolbox 1, to connect driving forces with pressures, classifying the state of the system and allowing the identification of target contaminants and the extent of contamination; (ii) Toolbox 2, to quantify bioaccumulation also by identifying corresponding areas; (iii) Toolbox 3, to identify the most suitable remediation solutions for previously identified contaminated areas, named contamination scenarios. The eDPSIR was calibrated on the case study of the Mar Piccolo in Taranto (Southern Italy), one of the most complex and polluted areas in Europe. While the consolidated DPSIR allows for a strategic response by limiting the use of contaminated areas or reducing upstream pressures, the eDPSIR made it possible to structure with a semi-quantitative logic the problem of assisting the decision-makers in choosing the optimal technological remediation responses for each sediment scenario of contamination (heavy metal; organic compounds; mixed). Assisted natural attenuation was identified as the best remediation technology in terms of treatment effectiveness and smallest amount of impacts involved in the project actions. However, considering the scenario of mixed contamination, in-situ reactive capping reached a good rank with a value of the composite indicator equal to 99.5%; thermal desorption and stabilization/solidification recorded a value of 94.1% and 84.6%, respectively. The application of these toolboxes provides alternative means to interpret, manage, and solve different cases of global marine contaminated sites. Graphical abstract: Image 1 Highlights: eDPSIR is the Engineered version of Drivers Pressures States Impacts Response model. eDPSIR boosts cause-effect relationships through three multidisciplinary toolboxes. eDPSIR fits synergistically into the DPSIR logic-based decision support system. The identification of remediation technological responses is its final goal. eDPSIR logic can include local stakeholders in the decision-making process. Abstract : To develop and apply a new DPSIR-based decision-making approach capable of structuring and solving a complex problem such as heavily contaminated coastal areas.